INFLUENCE OF INFRASTRUCTURAL FACILITIES ON THE MANAGEMENT OF SECONDARY SCHOOLS IN BENUE STATE, NIGERIA - ezekiel, Ivagher; TONDO ABRAHAM, INDYAR,; JACKSON TER INGURAN, AZEVER,; THERESA UJU, ONYEANISI (IJRDO- Journal of Educational Research, 2018)
This study investigated the influence of infrastructural facilities on the management of public secondary schools in Benue State. Two research questions and two hypotheses guided the study. Descriptive survey research design was adopted for the study. The population of the study comprised 5,110 teachers from 297 public secondary schools in Benue State. Four hundred teachers from 30 public secondary schools constituted the sample of the study. A- 10 item structured questionnaire constructed by the researcher titled Infrastructural Facilities Questionnaire (IFQ) was used for collection of data for the study. A pilot study was conducted to establish the reliability of the instrument which yielded 0.82. Data collected were analyzed using descriptive statistics of mean and standard deviation to answer research questions while the chi-square χ2 test of goodness of fit were used to test the hypotheses at 0.05 level of significance. The findings revealed that school libraries and school laboratories significantly influenced the management of public secondary schools in Benue State. Based on the findings of the study, it was recommended among other things that school administrators should ensure that school library is built and well equipped with books to enhance effective teaching and learning in the school.